Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) sebagai Upaya Pencegahan Stunting melalui Kegiatan Edukasi di SD Negeri Tunfeu 2 Kabupaten Nekamese - Nabilah Nurul Ilma; Odi L. Namangdjabar; Hasri Yulianti; Nurlaelah Al-Tadom; Adriana M.S. Boimau (Health Care : Journal of Community Service, 2025)
Stunting is a chronic nutritional problem that poses a major challenge to the development of quality human resources. The condition is not only influenced by inadequate nutritional intake, but also by environmental and behavioral factors. One of the factors that contribute to stunting is the low level of Clean and Healthy Living Behavior (PHBS), especially the habit of washing hands properly. Previous studies confirm that proper handwashing behavior, as part of Clean and Healthy Living Behavior (PHBS), has a significant correlation with reducing stunting. In addition to nutritional interventions, stunting prevention also requires changes in community behavior (PHBS) through effective education. The purpose of this community service activity is to increase elementary school students' knowledge about PHBS as an effort to prevent stunting. The implementation method includes educational counseling, discussion, six-step hand washing simulation, and evaluation through pre-test and post-test. The results of the activity showed an increase in participants' knowledge, where students with good knowledge increased by 73%, and students with poor knowledge decreased to 7%. In addition, students' hand washing practice skills also showed improvement. PHBS education carried out from an early age has proven to be effective in shaping hygienic behavior and supporting efforts to reduce the prevalence of stunting in the future.